Concordance between self-reported and actigraphy-assessed sleep duration among African-American adults: findings from the Jackson Heart Sleep Study. Issue 3 (16th October 2019) - Jackson, Chandra L; Ward, Julia B; Johnson, Dayna A; Sims, Mario; Wilson, James; Redline, Susan
Abstract: Study Objectives: Most epidemiological studies assess sleep duration using questionnaires. Interpreting this information requires understanding the extent to which self-reported habitual sleep reflects objectively assessed sleep duration, particularly among African Americans, who disproportionately experience poor sleep health. Methods: Among African-American participants of the Jackson Heart Sleep Study, we investigated differences in questionnaire-based self-assessed average sleep duration and self-assessed wake-bed time differences compared to actigraphy-based assessments of total sleep time (TST) and average time in bed (TIB). Linear regression models provided estimates of concordance between actigraphy-based and self-reported sleep duration. Results: Among 821 adults, self-assessed average sleep duration was lower than self-assessed wake-bed time differences (6.4 ± 1.4 vs. 7.5 ± 1.7 h, p < 0.0001). Mean actigraphy-based TST was 6.6 ± 1.2 h, and actigraphy-based average TIB was 7.6 ± 1.2 h. Self-assessed average sleep duration and actigraphy-based TST were moderately correlated ( r = 0.28, p < 0.0001). Self-assessed average sleep duration underestimated actigraphy-based TST by −30.7 min (95% confidence intervals [CI]: −36.5 to −24.9). In contrast, self-assessed wake-bed time differences overestimated actigraphy-based TST by 45.1 min (95% CI: 38.6–51.5). In subgroup analyses, self-assessed average sleep duration underestimated actigraphy-based measures most strongly among participants with insomnia symptoms. Conclusions: Among African Americans, self-assessed average sleep duration underestimated objectively measured sleep while self-assessed wake-bed time differences overestimated objectively measured sleep. Sleep measurement property differences should be considered when investigating disparities in sleep and evaluating their associations with health outcomes.